Bibliometric analysis of stroke and quality of life - Chen, Mengtong; Zhang, Yuting; Dong, Lijuan; Guo, Xiaomei (Frontiers in Neurology, 2023)
Abstract Objective: To perform a bibliometric analysis of stroke and quality of life studies between 2000 and 2022 using VOSviewer and CiteSpace. Methods: The literature data source for this study was the Web of Science Core Collection. CiteSpace and VOSviewer were used to analyze publications in relation to authors, countries, institutions, journals, references, and keywords. Results: A total of 704 publications were obtained for the bibliometric analysis. The number of publications has gradually increased over 23 years, with an annual increase of 728.6%. KIM S is the most prolific author in the field (10 publications), and the United States and Chinese Univ Hong Kong have the most publications. Stroke is the most prolific journal with the most citations per paper (91.58) and the highest impact factor(IF 2021, 10.17). The most high-frequency keywords are “stroke”, “quality of life”, “rehabilitation”, and “depression”. Conclusion: A bibliometric analysis of stroke and quality of life over the last 23 years provides future research directions.